2017
DOI: 10.1002/pbc.26533
|View full text |Cite
|
Sign up to set email alerts
|

Childhood osteosarcoma: Incidence and survival in Argentina. Report from the National Pediatric Cancer Registry, ROHA Network 2000–2013

Abstract: In Argentina, ASR of osteosarcoma is similar to that in high-income countries, but survival is lower in all regions. Future work will focus on identification and reduction of causes of preventable treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…In our study, survival rates in children diagnosed with osteosarcoma are low and comparable with other studies conducted in LMIC . Abandonment of treatment is a major issue in our country, as previously reported, and represents a major contributing factor of worse prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, survival rates in children diagnosed with osteosarcoma are low and comparable with other studies conducted in LMIC . Abandonment of treatment is a major issue in our country, as previously reported, and represents a major contributing factor of worse prognosis.…”
Section: Discussionsupporting
confidence: 88%
“…OS is the second leading cause of cancer-associated mortality among young individuals worldwide; [3][4][5] however, the underlying mechanism that modulates its occurrence and pathophysiology remains unclear. Merlin has been identified as an anti-oncogene 31,32 and plays an essential role in OS.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] OS primarily affects young individuals, and is the second leading cause of cancer-associated mortality in children and adolescents worldwide. 4,5 The 5-year overall survival rate of OS has increased to approximately 6070% owing to the considerable advances in surgical technologies and combined therapeutic strategies. 6 However, the survival rate remains poor in patients at advanced clinical stages and with pulmonary metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is the most common tumor of the bone in adolescents [ 1 , 2 ]. The incidence of patients aged 0-24 years was between 2.0% and 7.6% depending on the regions [ 3 ]. It was reported that there were about 20% of osteosarcoma patients presenting clinical metastasis to the lungs at the time of initial examination and the 5-year survival rate was less than 20% in these patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%